Estimating the fraction of unreported infections in epidemics with a known epicenter: An application to COVID-19 - Ali Hortaçsu; Jiarui Liu; Timothy Schwieg (Centre for Microdata Methods and Practice (cemmap), 2020)
We develop an analytically tractable method to estimate the fraction of unreported infections in epidemics with a known epicenter and estimate the number of unreported COVID-19 infections in the U.S. during the first half of March 2020. Our method utilizes the covariation in initial reported infections across U.S. regions and the number of travelers to these regions from the epicenter, along with the results of an early randomized testing study in Iceland. Using our estimates of the number of unreported infections, which are substantially larger than the number of reported infections, we also provide estimates for the infection fatality rate using data on reported COVID-19 fatalities from U.S. counties.
Keywords: 330; Coronavirus; Sterblichkeit; Messung; Schätzung; USA